An algebraic expression is a statement containing all possible combinations of variables, constants and operators. Factoring is a technique in driving the factors of a algebraic expression. An algebraic expression may be subjected into different operations and can be simplified, translated and evaluated. Algebraic expressions can be factored by applying common monomial factoring using greatest common factor, applying factoring bionomials like the difference of two square, sum and difference of two cubes, of two prime powers and of two composite powers, applying factoring trinomials.

Given 3x

Algebraic expression has two variables, having constants and the terms are connected by addition/subtraction operators.

Step 2:

Finding the GCF of the constants and the variables one by one.

The GCF of the constants in 3, 9 and 12 is 3, because only 3 can divide all the numbers 3, 9 and 12.

=> GCF(3, 9, 12) = 3

Step 3:

The GCF of the variable ‘x’ in x

The GCF of the variable ‘y’ in x

Step 4:

The given expression can therefore be written by factoring as,

=> 3x

Now by using distributive property, it can be simplified as,

=> 3xy(x – 3 + 4y)

or 3xy(x + 4y – 3).

=> 3x

Given x

This has no common monomial factor

Step 2:

Solve for x,

=> x

= x(x - 12) - 3(x - 12)

= (x - 3)(x - 12)

=> x

Given 1 - 49y^{4}

Factorized, 1 - 49y^{4} => 1 - 49y^{4} = 1^{2} - (7y^{2} )^{2}

= (1 + 7y^{2} )(1 - 7y^{2} )

[ a^{2} - b^{2} = (a + b)(a - b) ]

The square root of 1 is 1, and the square root of 49y^{4} is 7y^{2}.

The sum (1 + 7y^{2}) and difference (1 - 7y^{2}) of the square root are the factors.

=> 1 - 49y^{4} = (1 + 7y^{2} )(1 - 7y^{2} ) **answer**

Factorized, 1 - 49y

= (1 + 7y

[ a

The square root of 1 is 1, and the square root of 49y

The sum (1 + 7y

=> 1 - 49y

Given 12x(x + 2)(x + 3)^{2} + 21(x - 4)(x + 3)

Find the common factors of given algebraic expression

=> 12x(x + 2)(x + 3)^{2} + 21(x - 4)(x + 3) = 3 * 4 * x (x + 2)(x + 3)^{2} + 3 * 7(x - 2^{2})(x + 3)

= 3 * 4 * x (x + 2)(x + 3)^{2} + 3 * 7(x - 2)(x + 2)(x + 3)

Algebraic expression has as a common factor = 3(x + 2)(x + 3)

= 3(x + 2)(x + 3){4x(x + 3) + 7(x - 2)}

=> 12x(x + 2)(x + 3)^{2} + 21(x - 4)(x + 3) = 3(x + 2)(x + 3){4x(x + 3) + 7(x - 2)}.

Find the common factors of given algebraic expression

=> 12x(x + 2)(x + 3)

= 3 * 4 * x (x + 2)(x + 3)

Algebraic expression has as a common factor = 3(x + 2)(x + 3)

= 3(x + 2)(x + 3){4x(x + 3) + 7(x - 2)}

=> 12x(x + 2)(x + 3)